Exploring the relationship between gut microbiota and breast diseases using Mendelian randomization analysis - Wang, Xin; Gao, Haoyu; Zeng, Yiyao; Chen, Jie (Frontiers in Medicine, 2024)
Background Growing evidence suggests a relationship between gut microbiota composition and breast diseases, although the precise nature of this association remains uncertain. To investigate the causal relationship between gut microbiota and breast diseases, we utilized two-way Mendelian randomization (MR) analysis. Methods Four common diseases were included as outcomes: breast cancer, breast cysts, inflammatory disorders of the breast, and infections of the breast associated with childbirth, along with their subtypes. Genetic data on gut microbiota were extracted from genome-wide association studies (GWAS). The primary approach used to investigate the association between these genetic factors and gut microbiota was the inverse-variance-weighted (IVW) method with random-effects types. Sensitivity analyses, such as Cochran’s Q test, the MR-Egger intercept test, and leave-one-out analysis, were conducted to ensure the stability and reliability of the MR findings. Results We discovered plausible causal links between 20 microbial categories and the breast diseases, with a significance level of p < 0.05. Notably, Family.Rikenellaceae (p: 0.0013) maintained a significant inverse relationship with overall breast cancer (BC), after the Bonferroni correction. In the reverse MR analysis, interactions were observed between Genus.Adlercreutzia and estrogen receptor-positive cancer. In addition, Genus.Sellimonas, Family.Rikenellaceae, and Genus.Paraprevotella were associated with ER+ and overall breast cancer, whereas Genus.Dorea was linked to both estrogen receptor-negative and overall breast cancer. Family.Prevotellaceae was the only category correlated with inflammatory breast disorders. Moreover, Genus Eubacteriumruminantiumgroup, Genus.Lactococcus, and Family.Alcaligenaceae were associated with breast cysts, while Genus.Anaerofilum, Genus.Butyricimonas, Order.Coriobacteriales, Order.Pasteurellales, and Order.Verrucomicrobiales showed significant associations with infections of the breast associated with childbirth. No evidence of heterogeneity or horizontal pleiotropy was found. Conclusion Our Mendelian randomization analysis confirmed a causal relationship between gut microbiota and breast diseases. Early stool tests may be a viable method for screening diseases to identify people at higher risk of breast diseases.